Linking open innovation, entrepreneurial orientation and firm performance in Brazilian startups - Carvalho, Eduardo Gomes (2016)
The organizations are changing their business model from a traditional vertical integration model with internal research and development activities to an open business model, i.e., they are using open innovation. However, the main stream of studies about open innovation does not approach small and medium enterprises and it has had a limited impact upon the broader disciplines of management and economics. In addition, there are few studies about open innovation in Latin American countries. In Brazil, small and medium enterprises have an important role in the economic and social context, by GDP (Gross Domestic Product) participation and job generation. On the other hand, the interrelationship between innovation and entrepreneurship has become apparent through a vibrant research trend that fuses insights from different academic approaches. The purpose of this work is to check the relationship between entrepreneurial orientation, open innovation and firm performance in Brazilian startups. The thesis advocated is that dimensions of entrepreneurial orientation are drivers to macroprocess of open innovation, having both positive impact on firm performance. In addition, it is expected more impact on firm performance from macroprocess of open innovation than the dimensions of entrepreneurial orientation. The thesis adopts a pragmatic philosophical view and uses sequential exploratory mix-methods research to propose and examine theory. The exploratory design begins with and prioritizes the collection and analysis of qualitative data in the first phase, using muticase studies. One pilot study case was important to develop the research framework and protocol. Five startups compose the research universe in the first phase. Building from the exploratory results, in the second phase collects quantitative data to test or generalize the initial findings. After successive refinements, data from 94 startups were used in the second phase. The data was analyzed using multivariate data analysis, including structural equation modeling. The evidences point to situation where some dimensions of entrepreneurial orientation have impact on firm performance and are drivers for open innovation, while just outbound open innovation impacts firm performance.